Miejskie plany adaptacji do zmian klimatu w świetle nowelizacji ustawy z dnia 27 kwietnia 2001 r. – Prawo ochrony środowiska - Dąbrowski, Tomasz (PRAWO i WIĘŹ, 2025)
The article analyzes the legal aspects of municipal climate change adaptation plans. In accordance with the Act of 27 November 2024 on the amendment of the Environmental Protection Law and certain other acts, municipal climate change adaptation plans will become an important strategic document adopted by municipalities. Under the amendment to the Environmental Protection Law, municipalities are obligated to adopt municipal climate change adaptation plans for cities with a population of 20,000 or more. The legislator has specified, in particular, the structure and content of the plans, the procedure for their adoption, the method of ensuring public participation in the decision-making process, as well as the means of monitoring and reporting. The introduced regulations constitute a significant element in the reorganization of the role of local self-government in the environmental protection system. However, it is necessary to point out the structural flaws of this solution, including the lack of sanctions for failure to meet the deadlines for adopting the plans.